Lexical bundles in accepted and rejected Scopus-indexed hard science research article introductions - Eri Kurniawan; Cicih Permatasari (Studies in English Language and Education, 2025)
Lexical bundles are essential components of academic discourse, contributing to linguistic fluency in written and spoken communication. Their role is particularly crucial in publishing research articles in high-impact international journals. While previous studies have explored lexical bundle usage across various sections of research articles, little research has compared their use in accepted versus rejected introductions. This study aims to address this gap by examining the similarities and differences in lexical bundle usage within the introductions of accepted and rejected hard science research articles written by Indonesian scholars. This study employs a mixed-methods comparative research design. It analyzes 30 research article introductions from a hard science Scopus-indexed journal based on Bibers structural (noun/prepositional phrase-based) and Hylands functional (research-oriented, text-oriented, participant-oriented) frameworks. The findings indicate that accepted introductions contain a higher frequency of four-word lexical bundles. Structurally, both datasets are dominated by noun/prepositional phrase bundles and research-oriented bundles, but accepted introductions feature more structurally complete units. Functionally, research-oriented bundles are the most prevalent in both groups, emphasizing research processes and results in hard science writing. However, distinct differences in structural and functional subcategories suggest that proficiency in formulaic expressions may influence manuscript acceptance. This study contributes to understanding lexical bundle use in academic writing and provides practical implications for writing pedagogy, particularly for non-native scholars seeking publication in international journals.